Hambatan dan solusi pelaksanaan sita eksekutorial dalam perkara waris di Indonesia - aktafina, adibah alya (Maliki Interdisciplinary Journal, 2026)
The implementation of executorial seizure in inheritance cases in Indonesia is a crucial stage in realizing a legally binding court decision. This study aims to analyze obstacles and formulate solutions in the implementation of executorial seizure of inherited assets. The method used is normative juridical with a statutory and conceptual approach. The study results indicate that obstacles to executorial seizure encompass both juridical and non-juridical aspects. Legally, obstacles include resistance from the executing party (partij verzet), resistance from a third party (derden verzet), unclear status of the object of execution, non-compliance with court decisions, and judicial review efforts. Non-juridical obstacles include social and emotional conflicts between heirs, which delay the execution process. Resolution is achieved through legal procedural resistance mechanisms, postponement of execution, re-examination of the seized object, and a judge’s decision on the filed resistance. Once the obstacles are resolved, the execution is carried out under court supervision to ensure order and legal certainty. Thus, the success of an executory seizure in an inheritance case is determined by the clarity of the legal object, the compliance of the parties, and the effectiveness of the court’s role in managing the conflict.